2008
DOI: 10.1042/cs20080075
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of ursodeoxycholic acid decreases portal pressure in rats with biliary cirrhosis

Abstract: Liver cirrhosis is characterized by increased IHR (intrahepatic resistance) and lipid peroxidation, and decreased antioxidative defence. The present study investigates the effects of administration for 1 month of the antioxidant UDCA (ursodeoxycholic acid) in BDL (bile-duct-ligated) cirrhotic rats. Splanchnic haemodynamics, IHR, hepatic levels of TBARS (thiobarbituric acid-reacting substances), GSH (glutathione), SOD (superoxide dismutase) activity, nitrite, PIIINP (N-terminal propeptide of type III procollage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…It has been recently shown that chronic oral administration of UDCA decreases portal pressure, NO production and iNOS expression in BDL cirrhotic rats. 39 In our model, the administration of TUDCA reduced NO production to some extent, although no effect was observed on Nos2 mRNA levels. Conceivably, the full effect of TUDCA on NO production and iNOS expression may only be observed when cirrhosis develops.…”
Section: Protein S-nitrosation During Cholestasismentioning
confidence: 92%
“…It has been recently shown that chronic oral administration of UDCA decreases portal pressure, NO production and iNOS expression in BDL cirrhotic rats. 39 In our model, the administration of TUDCA reduced NO production to some extent, although no effect was observed on Nos2 mRNA levels. Conceivably, the full effect of TUDCA on NO production and iNOS expression may only be observed when cirrhosis develops.…”
Section: Protein S-nitrosation During Cholestasismentioning
confidence: 92%
“…Thus, Schiedermaier et al . reported a decrease in diastolic blood pressure but not portal flow in a small human cross‐over study, while Yang et al . described a reduction in portal pressure due to diminished intrahepatic resistance in a rat model.…”
Section: Bile Acids and Cardiovascular Functionmentioning
confidence: 95%
“…Murine liver sample sections were formalin‐fixed, paraffin‐embedded, and stained with hematoxylin–eosin, IFNγ, SOD, and Sirius Red. The samples embedded in optimal cutting temperature (OCT) compound were stained with Oil red O; NAFLD activity scores (NAS) were applied to evaluate hepatic steatosis and NASH . In addition, OCT‐embedded cryostat liver sections were used to investigate the hepatic infiltration of leukocytes and M1 KCs, which were stained by single fluorescein‐isothiocyanate (FITC)‐conjugated CD68 antibody and first FITC‐conjugated F4/80 antibody followed by second phycoerythrin‐conjugated CD11c antibody, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The samples embedded in optimal cutting temperature (OCT) compound were stained with Oil red O; NAFLD activity scores (NAS) were applied to evaluate hepatic steatosis and NASH. 25 In addition, OCTembedded cryostat liver sections were used to investigate the hepatic infiltration of leukocytes and M1 KCs, which were stained by single fluorescein-isothiocyanate (FITC)conjugated CD68 antibody and first FITC-conjugated F4/80 antibody followed by second phycoerythrinconjugated CD11c antibody, respectively. After counterstained with Fluoromount-G medium (SouthernBiotech, Birmingham, AL, USA), each slide was evaluated for the numbers of CD68 + cells per 1 mm 2 in the single FITC images.…”
Section: Liver Histopathological and Immunohistochemical Evaluationsmentioning
confidence: 99%